Students’ Problem Solving Skill on the Ecosystem Materials Through Somatic, Auditotry, Visual and Intellectual Model - Revi Handini*; Nur Aeni Ariyanti; Fauzan Kurniawan (Universitas Syiah Kuala, 2023)
The ability to problem solving is one of the higher order thinking skills so it is very important in biology learning. Based on observations, many students have low problem solving skills on the biology learning, especially in the ecosystem materials. This study aims to determine whether the somatic, auditory, visual, and intellectual (SAVI) model is effective to improve students' problem solving skills on the concept of the ecosystem. This study used a quasy experiment, and research design of the matching only pretest-posttest design. This study's population was all 10th-grade students MIPA of Senior High School of Prambanan in Sleman Regency, Indonesia. Sample selection using a random sampling technique from the entire population of class X MIPA, resulting in class X-4 MIPA being chosen as a control group and class X-2 MIPA as an experimental group. Data analysis in this study consisted of two, namely the N-Gain test and hypothesis testing using the independent samples t-test test. The results showed that the results of the N-Gain test in the experimental class were 0.73 (high category), while the control class is a score of 0.59 (medium category). Meanwhile, The results of the research on the independent samples t-test on problem solving skills are the sig value. 0.001, p 0,05. Based on results, it can be concluded that the SAVI model was effectively used in biology learning to improve problem solving skills